SEPBO: Trash separator bot VR game - Thirada Theethum; Sopoat Iamcharoen; Attawut Arpornrat; Sirion Vittayakorn (My University, 2021)
Everyday hundreds of thousands of tons of waste goes to landfills, although more than half of it could be either recycled or composted. The waste management situation tends to get worse when there are many poorly-designed landfill sites that could either leak hazardous chemicals which can contaminate groundwater or emit harmful gases into the atmosphere. These health hazards or environmental chain problems could be diminished if everyone sorted their waste precisely. To mitigate this problems, we aim to tackle it from the beginning. Thus, in this work, we propose a computer-based VR game called SEPBO. SEPBO is an educational game which aims not only for enjoyment, but also to improve the players' waste sorting skills. The experimental results confirm that SEPBO is a better tool to improve the players' waste sorting skill compared to the interactive web-based baseline, ReCollect: The Waste Sorting Game, in ALL aspects: with 6.67% higher performance in improving players' waste sorting skill and a 48% greater degree of satisfaction than the baseline in terms of enjoyment.
Keywords: Educational Games and Gamification; Augmented Reality Applications; Virtual Reality Applications and Impacts